2020
DOI: 10.20944/preprints202005.0152.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Acceptance of Face Mask Practice among Individuals Visiting Hospital during COVID-19 Pandemic: An Observational Study

Abstract: Background: The COVID-19 transmission has been established to occur through respiratory droplets from coughing and sneezing. Health agencies have strongly recommended the use of facemask as a precaution from cross-transmission. Objective: This study investigated the prevalence of facemask use among visitors to the hospital. This study also investigated the demographic factors contributing to unacceptable facemask practice. Setting: This prospective observational study was done among hospital visitors to a dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
4
18
3
Order By: Relevance
“…In the present study the prevalence of facemask usage was much lower than the rates from Hong Kong study among pedestrians [15], Malaysia study among hospital visitors [16] and Malaysia study on general public at wet markets [17] 94.8%, 96.9% and 99.7% respectively. Similar to our nding observed in Bangkok airport (46%) [18].…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In the present study the prevalence of facemask usage was much lower than the rates from Hong Kong study among pedestrians [15], Malaysia study among hospital visitors [16] and Malaysia study on general public at wet markets [17] 94.8%, 96.9% and 99.7% respectively. Similar to our nding observed in Bangkok airport (46%) [18].…”
Section: Discussioncontrasting
confidence: 53%
“…The percentage of acceptable face mask practice in our study was lower than some similar studies. This rates were reported from Malaysia about 95.63% and 88.75% [16,17] and from Hong Kong about 87 % [15] . Besides, we found that the correct practice of face mask use in women was higher than men.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The statistics of Malaysian population with regards to mask adherence was around 97% despite having high number of cases. However, the study showed that vulnerable population do not practice face mask and mortality rate was highest among these groups (18). The present data also revealed that in Indian population, religion, area of residence, employment status and high monthly income were signi cant factors in mask adherence.…”
Section: Discussionmentioning
confidence: 46%